System of Generating Japanese Sound Symbolic Expressions Using Genetic Algorithm - Shimizu, Yuichiro; Nakamura, Tetsuaki; Sakamoto, Maki (Human-Computer Interaction. Interaction Modalities and Techniques, 2013)
Japanese has a large number of sound symbolic words, onomatopoeia, which associates between sounds and sensory experiences. According to previous studies, a quantification of relationship between phonemes and images enables to predict the images evoked by onomatopoeia and to estimate meanings of onomatopoeia. In this study, we applied the quantification method and developed a system for generating Japanese onomatopoeias using genetic algorithm (GA). Our method uses 90 SD scales for expressing various impressions and genes for genetic algorithm which denote each phonological symbol in Japanese. Through genetic algorithm, the system generates and proposes onomatopoeias appropriate for impressions inputted by users. From the evaluation of our system, impressions of onomatopoeias generated by our method were similar to inputted impressions to generate onomatopoeias.